Positive electrode for lithium-sulfur secondary battery and lithium-sulfur secondary battery including the same

JP7645356B2Active Publication Date: 2025-03-13LG ENERGY SOLUTION LTD +1
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2023505915
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-10-22
Filing Date
2021-10-18
Publication Date
2025-03-13
Estimated Expiration
2041-10-18

AI Technical Summary

Benefits of technology

【0024】 本発明に係るリチウム-硫黄二次電池用正極は、簡単に多価金属塩を導入することによって、電極の重量を大きく増加させることなく、電極の伝導性を大きく低下させないながらも、電池に適用時、リチウムポリスルフィドの溶出を効果的に抑制し、リチウム-硫黄二次電池の性能を向上させることができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007645356000001
    Figure 0007645356000001
  • Figure 0007645356000002
    Figure 0007645356000002
  • Figure 0007645356000003
    Figure 0007645356000003
Patent Text Reader

Abstract

The present invention provides a positive electrode for a lithium-sulfur secondary battery, which includes a positive electrode active material, a conductive material, a binder, and a polyvalent metal salt. The polyvalent metal salt includes a cation of a metal selected from period 3 and period 4 metals whose outermost electrons have an effective nuclear charge of 3 to 6. The introduction of the polyvalent metal salt into the positive electrode for a lithium-sulfur secondary battery significantly reduces the conductivity of the electrode without significantly increasing the weight of the electrode, while effectively suppressing the elution of lithium polysulfide when used in the battery, thereby improving the performance of the lithium-sulfur secondary battery.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a positive electrode for a lithium-sulfur secondary battery and a lithium-sulfur secondary battery including the same. Specifically, the present invention relates to a positive electrode for a lithium-sulfur secondary battery including a polyvalent metal salt and a lithium-sulfur secondary battery including the same.

[0002] This application claims the benefit of priority based on Korean Patent Application No. 10-2020-0137322 filed on October 22, 2020, and incorporates all contents disclosed in the documents of said Korean patent application as part of this specification. [Background technology]

[0003] As the application area of ​​secondary batteries expands to electric vehicles (EVs) and energy storage systems (ESSs), lithium-ion secondary batteries, which have a relatively low energy storage density relative to weight (~250Wh / kg), have limitations in their application to such products. In contrast, lithium-sulfur secondary batteries are theoretically capable of realizing a high energy storage density relative to weight (~2,600Wh / kg), and are therefore in the spotlight as a next-generation secondary battery technology.

[0004] Lithium-sulfur secondary batteries refer to battery systems that use sulfur-based materials with S-S bonds as the positive electrode active material and lithium metal as the negative electrode active material. Sulfur, the main material of the positive electrode active material, is an abundant resource worldwide, and has the advantages of being non-toxic and having a low atomic weight.

[0005] During discharge, lithium, the negative electrode active material, loses electrons and is oxidized while ionizing, while the positive electrode active material, the sulfur-based material, receives electrons and is reduced. Here, the lithium oxidation reaction is the process in which lithium metal loses electrons and is converted into lithium cation form. Meanwhile, the sulfur reduction reaction is the process in which the S-S bond receives two electrons and is converted into sulfur anion form. The lithium cations produced by the lithium oxidation reaction are transferred to the positive electrode via the electrolyte and combine with the sulfur anions produced by the sulfur reduction reaction to form a salt. Specifically, sulfur before discharge has a cyclic S8 structure, which is reduced to lithium polysulfide (LiS x When the lithium polysulfides are completely reduced, lithium sulfide (Li2S) is produced.

[0006] Lithium-sulfur secondary batteries have problems such as low electrical conductivity of sulfur, dissolution of lithium polysulfide and volume expansion during charging and discharging, which can result in low coulombic efficiency and rapid capacity loss during charging and discharging. These problems must be solved to improve the performance of the battery.

[0007] Porous carbon materials are widely used in lithium-sulfur secondary batteries because they combine with sulfur, the active material in lithium-sulfur secondary batteries, to provide conductivity. Research is ongoing to improve battery performance by adjusting the size and volume of the pores formed inside such porous carbon materials. Among these, in the case of metal-organic frameworks (MOFs), pores of various sizes are formed depending on the types of organic molecules and metal atoms that make up the MOF, and the size can range from 1,000 to 4,000 m. 2The advantage of this method is that it can synthesize a porous carbon material with a high specific surface area (S / g). However, in the case of the conventional technology of carbonizing MOF materials and applying them to lithium-sulfur secondary batteries, even if the problem of lithium polysulfide leaching can be improved to some extent, the additional use of MOF materials with low conductivity can increase the overall weight of the electrode and reduce the conductivity of the electrode. Furthermore, this technology requires a complicated manufacturing process.

[0008] Therefore, research into improving the performance of lithium-sulfur secondary batteries has been continuously conducted in the art. [Prior art documents] [Non-patent literature]

[0009] [Non-Patent Document 1] Jianming Zheng et al.,Lewis Acid-Base Interactions between Polysulfides and Metal Organic Framework in Lithium Sulfur Batteries,Nano Lett.2014,14,2345-2352 [Non-Patent Document 2] Junwen Zhou et al.,Rational Design of a Metal-Organic Framework Host for Sulfur Storage in Fast,Long-Cycle Li-S Batteries,Energy Environ.Sci.,2014, 7, 2715 Summary of the Invention [Problem to be solved by the invention]

[0010] In order to solve the above problems, the present invention provides a positive electrode for a lithium-sulfur secondary battery that can improve the cycle performance of the battery by introducing a polyvalent metal salt into the positive electrode. [Means for solving the problem]

[0011] According to a first aspect of the present invention, The present invention provides a positive electrode for a lithium-sulfur secondary battery, comprising a positive electrode active material, a conductive material, a binder, and a polyvalent metal salt.

[0012] In one embodiment of the present invention, the polyvalent metal salt comprises a cation of a metal selected from period 3 and period 4 metals having an effective nuclear charge of 3 to 6 at the outermost electron.

[0013] In one embodiment of the present invention, the polyvalent metal salt is Mg 2+ and Al 3+ and a cation selected from the group consisting of OH - , CO3 2- , NO3 - and SO4 2- The anion is selected from the group consisting of:

[0014] In one embodiment of the present invention, the binder is a polymeric compound having a functional group containing oxygen or nitrogen.

[0015] In one embodiment of the present invention, the binder is selected from polyacrylic acid, polyvinyl alcohol, polyacrylonitrile, and combinations thereof.

[0016] In one embodiment of the present invention, the polyvalent metal salt is contained in an amount of 30 to 100 mol % based on the number of moles of the polymer monomer of the binder.

[0017] In one embodiment of the present invention, the positive electrode active material is selected from elemental sulfur (S8), a sulfur-carbon composite, a sulfur-based compound, and combinations thereof.

[0018] In one embodiment of the present invention, the binder is contained in an amount of 5 to 20% by weight based on the total weight of the positive electrode active material.

[0019] In one embodiment of the present invention, the conductive material is selected from graphite, carbon black, conductive fibers, metal powders, carbon fluoride, conductive whiskers, conductive metal oxides, polyphenylene derivatives, and combinations thereof.

[0020] In one embodiment of the present invention, the conductive material is contained in an amount of 5 to 20% by weight based on the total weight of the positive electrode active material.

[0021] In one embodiment of the present invention, the polyvalent metal salt is added to the positive electrode in the form of an aqueous solution and then dried.

[0022] In one embodiment of the present invention, the polyvalent metal salt in the form of an aqueous solution is added before the mixture of the positive electrode active material, the conductive material and the binder is dried, or is applied after the mixture is dried.

[0023] According to a second aspect of the present invention, A lithium-sulfur secondary battery including the above-described positive electrode is provided. Effect of the Invention

[0024] The positive electrode for a lithium-sulfur secondary battery according to the present invention can improve the performance of a lithium-sulfur secondary battery by simply introducing a polyvalent metal salt, without significantly increasing the weight of the electrode or significantly decreasing the conductivity of the electrode, and by effectively suppressing the elution of lithium polysulfide when applied to a battery. [Brief description of the drawings]

[0025] [Figure 1] 1 is a graph showing the results of thermogravimetric analysis of the sulfur-carbon composite according to Experimental Example 1. [Diagram 2] 1 is a graph showing the results of thermogravimetric analysis of a polyacrylic acid binder having polyvalent metal ions fixed thereto according to Experimental Example 2. [Diagram 3] 13 is a graph showing the results of an analysis of the capacity retention rate of a lithium-sulfur secondary battery according to Experimental Example 3. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0026] The embodiments provided by the present invention can all be achieved by the following description. It should be understood that the following description describes preferred embodiments of the present invention, and that the present invention is not necessarily limited thereto.

[0027] Unless the measurement conditions and methods are specifically described for the physical properties described in this specification, the physical properties are measured according to the measurement conditions and methods commonly used by a person of ordinary skill in the art.

[0028] The present invention provides a positive electrode for a lithium-sulfur secondary battery and a lithium-sulfur secondary battery including the same. Hereinafter, the positive electrode for a lithium-sulfur secondary battery according to the present invention and the remaining components of the lithium-sulfur secondary battery (negative electrode, separator, electrolyte) will be described in detail.

[0029] Positive electrode for lithium-sulfur secondary batteries The positive electrode for a lithium-sulfur secondary battery according to the present invention includes a positive electrode active material, a conductive material, a binder, and a polyvalent metal salt. The positive electrode may be divided into a positive electrode current collector and a positive electrode active material layer coated on the positive electrode current collector. In this case, the positive electrode active material, the conductive material, the binder, and the polyvalent metal salt are included in the positive electrode active material layer.

[0030] The positive electrode active material constituting the positive electrode for the lithium-sulfur secondary battery according to the present invention may be selected from elemental sulfur (S8), a sulfur-carbon composite, a sulfur-based compound, or a mixture thereof, but is not necessarily limited thereto. The sulfur-based compound is specifically Li2Sn (n≧1), an organic sulfur compound, or a carbon-sulfur polymer (C2S x ) n: x = 2.5 to 50, n ≧ 2). These sulfur materials alone do not have electrical conductivity, so they are used in combination with a conductive material. The sulfur-carbon composite is an embodiment of a positive electrode active material in which carbon is mixed with elemental sulfur or a sulfur-based compound to reduce sulfur leakage into the electrolyte and increase the electrical conductivity of the electrode containing sulfur. The ratio of the positive electrode active material in the positive electrode active material layer can be adjusted in consideration of the performance of the target battery. According to one embodiment of the present invention, the positive electrode active material layer contains 60 to 95 parts by weight of the positive electrode active material based on 100 parts by weight of the positive electrode active material layer.

[0031] The carbon material constituting the sulfur-carbon composite may be crystalline or amorphous carbon, or may be conductive carbon. Specifically, graphite, graphene, Super P, carbon black, denka black, acetylene black, ketjen black, channel black, furnace black, lamp black, summer black, carbon fiber, carbon nanofiber, carbon nanotube, carbon nanowire, carbon nanoring, carbon fabric, and fullerene (C 60 ) may be selected from the group consisting of.

[0032] An exemplary sulfur-carbon composite is a sulfur-carbon nanotube composite. Specifically, the sulfur-carbon nanotube composite includes a carbon nanotube aggregate having a three-dimensional structure, and sulfur or a sulfur compound on at least a part of the inner surface and the outer surface of the carbon nanotube aggregate. In the sulfur-carbon nanotube composite according to an embodiment of the present invention, since sulfur is present inside the three-dimensional structure of the carbon nanotube, even if soluble polysulfide is generated in an electrochemical reaction, if it can be located inside the carbon nanotube, the three-dimensional entangled structure can be maintained even when the polysulfide is dissolved, and the phenomenon of the collapse of the positive electrode structure can be suppressed. As a result, the lithium-sulfur secondary battery including the sulfur-carbon nanotube composite has an advantage that it can realize a high capacity even at high loading. In addition, the sulfur or sulfur-based compound can be provided in the internal pores of the carbon nanotube aggregate. The carbon nanotube means linear conductive carbon, and specifically, carbon nanotubes (CNT), graphitic nanofibers (GNF), carbon nanofibers (CNF) or activated carbon fibers (ACF) can be used, and both single-walled carbon nanotubes (SWCNT) and multi-walled carbon nanotubes (MWCNT) can be used.

[0033] According to one embodiment of the present invention, the sulfur-carbon composite is prepared by impregnating the outer surface and the inside of carbon with sulfur or a sulfur-based compound, and optionally, a step of adjusting the diameter of the carbon before, after, or both before and after the impregnation step. The impregnation step may be performed by mixing carbon and a sulfur or sulfur-based compound powder, and then heating the mixture to impregnate the carbon with the molten sulfur or sulfur-based compound. A dry ball mill method, a dry jet mill method, or a dry dyno mill method may be used for the mixing. According to one embodiment of the present invention, the sulfur-carbon composite contains 60 to 90 parts by weight of sulfur or a sulfur-based compound based on 100 parts by weight of the sulfur-carbon composite. When the content of the sulfur or sulfur-based compound in the sulfur-carbon composite is adjusted within the above range, the non-conductive material can appropriately supply electrons to the sulfur or sulfur-based compound while maintaining a high content of the sulfur or sulfur-based compound. The sulfur-carbon complex has a porosity of a certain level or more since the sulfur or sulfur-based compound is supported on the porous carbon. Therefore, even if the positive electrode active material layer is sufficiently rolled in a manner that maintains the structure of the sulfur-carbon composite, the impregnation of the electrolyte into the positive electrode active material layer does not decrease.

[0034] The conductive material constituting the positive electrode for the lithium-sulfur secondary battery according to the present invention may be selected from, but is not necessarily limited to, graphite such as natural graphite or artificial graphite; carbon black such as acetylene black, ketjen black, channel black, furnace black, lamp black, or summer black; conductive fiber such as carbon fiber or metal fiber; carbon fluoride; metal powder such as aluminum or nickel powder; conductive whisker such as zinc oxide or potassium titanate; conductive metal oxide such as titanium oxide; or polyphenylene derivatives. The proportion of the conductive material in the positive electrode active material layer is adjusted in consideration of the performance of the intended battery. According to one embodiment of the present invention, the positive electrode active material layer may contain 0.05 to 20 parts by weight, preferably 5 to 15 parts by weight of the conductive material based on 100 parts by weight of the positive electrode active material layer. The proportion of the conductive material is also adjusted based on the positive electrode active material. According to one embodiment of the present invention, the conductive material may be contained in an amount of 5 to 20% by weight, preferably 10 to 15% by weight, based on the total weight of the positive electrode active material.

[0035] The binder constituting the positive electrode for the lithium-sulfur battery according to the present invention basically has a function of assisting in binding the positive electrode active material and the conductive material and binding to the current collector, but in the present invention, in addition to the above function, it has an additional function of fixing the metal cation of the polyvalent metal salt. In order to have the above-mentioned functionality, the binder may be a polymer compound having a functional group containing oxygen or nitrogen. Oxygen or nitrogen atoms having high electronegativity are relatively rich in electrons in the polymer compound and tend to be negatively charged, and the metal cation is fixed to the binder by the electric attraction with the metal cation. According to one embodiment of the present invention, the binder may be selected from polyacrylic acid, polyvinyl alcohol, polyacrylonitrile, and combinations thereof, and may be preferably polyacrylic acid.

[0036] The binder may be used in combination with one or more binders selected from the group consisting of vinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinylidene fluoride, polymethylmethacrylate, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinylpyrrolidone, tetrafluoroethylene, polyethylene, polypropylene, ethylene-propylene-diene monomer (EPDM), sulfone EPDM, styrene-butylene rubber (SBR) and fluororubber, in order to supplement the binding force between the components constituting the positive electrode. The ratio of the binder in the positive electrode active material layer may be adjusted in consideration of the performance of the intended battery. According to one embodiment of the present invention, the positive electrode active material layer contains 1 to 30 parts by weight, preferably 3 to 20 parts by weight, more preferably 5 to 15 parts by weight of the binder based on 100 parts by weight of the positive electrode active material layer. The proportion of the binder may also be adjusted based on the positive electrode active material. According to one embodiment of the present invention, the binder is contained in an amount of 5 to 20 wt %, preferably 10 to 15 wt %, based on the total weight of the positive electrode active material.

[0037] The polyvalent metal salt constituting the positive electrode for the lithium-sulfur secondary battery according to the present invention includes a polyvalent metal cation having a valence of 2 or more. The polyvalent metal cation can be bound to a negative charge generated when sulfur or a sulfur-based material receives electrons and is reduced during discharge of the lithium-sulfur secondary battery by electrical attraction. However, since the polyvalent metal cation is not a macromolecule, it may flow out into the electrolyte at the positive electrode, and in order to fix the negative charge, the polyvalent metal cation must also be fixed to a macromolecule. The polyvalent metal cation can be fixed to the binder described above. A polymer compound having a functional group containing oxygen or nitrogen as a binder can have a negative charge at the oxygen or nitrogen portion having high electronegativity, and can fix the polyvalent metal cation by electrical attraction. Since the polyvalent metal cation has a polyvalent positive charge, even if it is bound to the binder by electrical attraction, it can maintain a part of the positive charge and fix the sulfur or sulfur-based material having a negative charge after discharge.

[0038] Even if the polyvalent metal salt contains a polyvalent metal cation, it does not have high functionality between the negatively charged positive electrode active material and the binder for improving the performance of a lithium-sulfur secondary battery, so the types of cations and anions constituting the polyvalent metal salt must be appropriately selected. According to one embodiment of the present invention, the polyvalent metal salt contains a cation of a metal selected from period 3 and period 4 metals whose effective nuclear charge of the outermost electron is 3 to 6, preferably 3 to 4.5. According to one embodiment of the present invention, the polyvalent metal salt contains Mg 2+ and Al 3+ and a cation selected from the group consisting of OH - , CO3 2- , NO3 - and SO4 2- and an anion selected from:

[0039] The content of the polyvalent metal salt can be determined by the content of the binder in the positive electrode active material layer. When the binder is a polymer compound having a functional group containing oxygen or nitrogen, the number of functional groups having functionality is important, so when determining the content of the polyvalent metal salt, the number of moles of the monomer of the polymer binder is the basis rather than the number of moles of the polymer binder. According to one embodiment of the present invention, the polyvalent metal salt may be contained in an amount of 30 to 100 mol% based on the number of moles of the polymer monomer of the binder. Specifically, the content of the polyvalent metal salt based on the number of moles of the polymer monomer of the binder is 30 mol% or more, 40 mol% or more, 50 mol% or more, 60 mol% or more, 70 mol% or more, 80 mol% or more, 90 mol% or more, and 100 mol% or less, 30 to 100 mol%, 50 to 100 mol%, or 70 to 100 mol%. If the content of the polyvalent metal salt exceeds 100 mol% based on the number of moles of the polymer monomer of the binder, the binder functional group cannot sufficiently fix the polyvalent metal cation, and if the content of the polyvalent metal salt is less than 30 mol% based on the number of moles of the polymer monomer of the binder, many binder functional groups are fixed to one polyvalent metal cation, and the polyvalent metal cation cannot sufficiently fix the negatively charged positive electrode active material.

[0040] The positive electrode is manufactured by applying a slurry containing a positive active material to one or both sides of a positive current collector to form a positive active material layer. The application can be performed by a method commonly known in the art, such as a doctor blade, die casting, comma coating, screen printing, etc. The polyvalent metal salt is added to the positive electrode in the form of an aqueous solution. The polyvalent metal salt in the aqueous solution is separated into polyvalent metal cations and anions, and the separated polyvalent metal cations are easily fixed to the binder. According to one embodiment of the present invention, the concentration of the polyvalent metal salt in the aqueous solution may be 0.05 to 0.5 M, preferably 0.1 to 0.3 M. The polyvalent metal salt in the aqueous solution may be added directly to the positive active material slurry of the positive active material, the conductive material, and the binder, or the slurry may be applied to the positive current collector, dried, and then applied onto the dried layer. If the polyvalent metal salt in the form of an aqueous solution is immediately added to the positive electrode active material slurry, the functional polyvalent metal salt can be uniformly dispersed in the positive electrode active material, which is more advantageous in improving the performance of the lithium-sulfur secondary battery.

[0041] Lithium-sulfur secondary battery The lithium-sulfur secondary battery of the present invention includes a positive electrode, a negative electrode, a separator, and an electrolyte. The positive electrode is as described above, and the negative electrode, separator, and electrolyte are described in detail below.

[0042] The negative electrode constituting the lithium-sulfur secondary battery according to the present invention includes a negative electrode current collector, and a negative electrode active material layer formed on the negative electrode current collector.

[0043] The negative electrode active material layer includes a negative electrode active material, a binder, and a conductive material. The negative electrode active material is lithium ion (Li + A material capable of reversibly intercalating or deintercalating ions (Cd), a material capable of reversibly forming a lithium-containing compound by reacting with lithium ions, lithium metal, or a lithium alloy can be used.

[0044] The lithium ion (Li + The material capable of reversibly absorbing and releasing lithium ions (Li) may be, for example, crystalline carbon, amorphous carbon, or a mixture thereof. + The material capable of reacting with lithium (Li) to reversibly form a lithium-containing compound may be, for example, tin oxide, titanium nitrate, or silicon. The lithium alloy may be, for example, an alloy of lithium (Li) and a metal selected from the group consisting of sodium (Na), potassium (K), rubidium (Rb), cesium (Cs), francium (Fr), beryllium (Be), magnesium (Mg), calcium (Ca), strontium (Sr), barium (Ba), radium (Ra), aluminum (Al), and tin (Sn).

[0045] The binder, conductive material, and negative electrode current collector may be selected with reference to the configuration of the positive electrode described above, but are not necessarily selected in the same manner as the positive electrode in specific examples. Also, the method of forming the negative electrode active material layer on the negative electrode current collector may be selected with reference to the method of the positive electrode described above, but are not necessarily selected in the same manner as the positive electrode in specific examples.

[0046] The separator of the lithium-sulfur secondary battery according to the present invention is a physical separator having a function of physically separating electrodes, and any separator commonly used in the art may be used without any particular limitation. In particular, a separator having low resistance to ion transfer in the electrolyte and excellent electrolyte humidification capability is preferred. The separator separates or insulates the positive and negative electrodes from each other while allowing lithium ions to be transported between the positive and negative electrodes.

[0047] Such a separator may be made of a porous material having a porosity of 30 to 50% and non-conductive or insulating properties. Specifically, a porous polymer film may be used, for example, a porous polymer film made of a polyolefin polymer such as an ethylene homopolymer, a propylene homopolymer, an ethylene / butene copolymer, an ethylene / hexene copolymer, or an ethylene / methacrylate copolymer, or a non-woven fabric made of a high melting point glass fiber. Among these, a porous polymer film is preferably used.

[0048] If both the buffer layer and the separator are made of polymer film, the electrolyte impregnation amount and ion conductivity are reduced, and the effect of reducing overvoltage and improving capacity characteristics is minimal. Conversely, if both are made of nonwoven fabric, mechanical rigidity cannot be ensured, and the problem of battery short circuit occurs. However, by using a film separator in combination with a polymer nonwoven fabric buffer layer, mechanical strength can be ensured while improving battery performance by using a buffer layer.

[0049] According to one embodiment of the present invention, an ethylene homopolymer (polyethylene) polymer film is used as a separator and a polyimide nonwoven fabric is used as a buffer layer, and the polyethylene polymer film preferably has a thickness of 10 to 25 μm and a porosity of 40 to 50%.

[0050] The electrolyte constituting the lithium-sulfur secondary battery according to the present invention is a non-aqueous electrolyte containing a lithium salt, and contains a lithium salt and a solvent.

[0051] The lithium salt is a material that can be easily dissolved in a non-aqueous organic solvent, for example, LiCl, LiBr, LiI, LiClO4, LiBF4, LiB 10 Cl 10, LiB(Ph)4, LiC4BO8, LiPF6, LiCF3SO3, LiCF3CO2, LiAsF6, LiSbF6, LiAlCl4, LiSO3CH3, LiSO3CF3, LiSCN, LiC(CF3SO2)3, LiN(CF3SO2)2, LiN(C2F5SO2)2, LiN(SO2F)2, lithium chloroborane, lithium lower aliphatic carboxylate, and lithium imide. In one embodiment of the present invention, the lithium salt is preferably lithium imide such as LiTFSI.

[0052] The concentration of the lithium salt may be 0.1-8.0M, preferably 0.5-5.0M, more preferably 1.0-3.0M, depending on various factors such as the exact composition of the electrolyte mixture, the solubility of the salt, the conductivity of the dissolved salt, the charge and discharge conditions of the battery, the operating temperature, and other factors known in the field of lithium secondary batteries. If the concentration of the lithium salt is below this range, the conductivity of the electrolyte may be low, which may reduce the battery performance, and if it exceeds this range, the viscosity of the electrolyte may increase, which may reduce the dispersal of the lithium ions (Li + ) may decrease the mobility, so it is preferable to select an appropriate concentration within the above range.

[0053] The solvent is not particularly limited as long as it is a non-aqueous solvent that serves as a medium through which ions involved in the electrochemical reaction of the battery can move. According to one embodiment of the present invention, the solvent may be a carbonate-based, ester-based, ether-based, ketone-based, alcohol-based, or aprotic solvent.

[0054] Specific examples of the carbonate-based solvent include dimethyl carbonate (DMC), diethyl carbonate (DEC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), methyl ethyl carbonate (MEC), ethylene carbonate (EC), propylene carbonate (PC), and butylene carbonate (BC).

[0055] Specific examples of the ester solvent include methyl acetate, ethyl acetate, n-propyl acetate, 1,1-dimethylethyl acetate, methyl propionate, ethyl propionate, γ-butyrolactone, decanolide, valerolactone, mevalonolactone, and caprolactone.

[0056] Specific examples of the ether solvent that can be used include diethyl ether, dipropyl ether, dibutyl ether, dimethoxymethane, trimethoxymethane, dimethoxyethane, diethoxyethane, diglyme, triglyme, tetraglyme, tetrahydrofuran, 2-methyltetrahydrofuran, and polyethylene glycol dimethyl ether.

[0057] Specifically, the ketone solvent may be cyclohexanone.

[0058] As the alcohol-based solvent, specifically, ethyl alcohol, isopropyl alcohol, etc. can be used.

[0059] As the aprotic solvent, specifically, nitriles such as acetonitrile, amides such as dimethylformamide, dioxolanes such as 1,3-dioxolane (DOL), sulfolane, etc. can be used.

[0060] The non-aqueous organic solvents can be used alone or in combination of one or more. When one or more are used in combination, the mixing ratio can be appropriately adjusted depending on the intended battery performance. In particular, a mixture of 1,3-dioxolane and dimethoxyethane in a volume ratio of 1:1 is preferred.

[0061] The lithium-sulfur secondary battery of the present invention may be manufactured by forming an electrode assembly by disposing a separator between a positive electrode and a negative electrode, and then inserting the electrode assembly into a battery case, such as a cylindrical or rectangular battery case, and then injecting an electrolyte into the battery case. Alternatively, the electrode assemblies may be stacked, impregnated with an electrolyte, and then inserted into a battery case and sealed.

[0062] Preferred examples are presented below to aid in understanding the present invention. However, the following examples are provided only to facilitate understanding of the present invention, and the present invention is not limited thereto.

[0063] Working Example Example 1 3g of Ketjen Black (manufacturer: MICHIBISHI CHEMICAL, specification: 600JD) and 9g of sulfur were dispersed in 200ml of toluene and heated and stirred at 60℃ for 3 hours. The powder obtained by evaporating the toluene was heated at 160℃ for 20 hours in an argon (condition: 100sccm) atmosphere to melt the sulfur and support it in the pores of the porous carbon material. The resultant was heated in a vacuum oven at 50℃ (condition: 1Pa or less) for 3 hours to produce a sulfur-carbon composite.

[0064] The sulfur-carbon composite (positive electrode active material) was mixed with Super P carbon black (manufacturer: TIMCAL, conductive material) and polyacrylic acid (molecular weight: M w 450k, binder) in a weight ratio of 8:1:1, and then 0.1M Al2(SO4)3 aqueous solution was further mixed with polyacrylic acid polymer monomer and Al2(SO4)3 in a molar ratio of 1:1 to prepare a slurry (mixing conditions: Elim Global 8000D, zirconia ball (1:1 mix of 6mm and 3mm diameters), polypropylene vial). The slurry was then applied to aluminum foil using a doctor blade (application amount: 1.7mg / cm based on sulfur weight). 2 (about 2mAh / cm 2)), then dried in air at 50°C and in vacuum at 50°C to prepare a positive electrode (effective nuclear charge of the outermost electron of Al: 4.066).

[0065] Example 2 A positive electrode was prepared in the same manner as in Example 1, except that a 0.2M MgSO4 aqueous solution was used instead of a 0.1M Al2(SO4)3 aqueous solution as the polyvalent metal salt aqueous solution (effective nuclear charge of the outermost electron of Mg: 3.308).

[0066] Example 3 A positive electrode was produced in the same manner as in Example 1, except that a 0.2 M ZnSO4 aqueous solution was used as the polyvalent metal salt aqueous solution instead of a 0.1 M Al2(SO4)3 aqueous solution (effective nuclear charge of the outermost electron of Zn: 5.965).

[0067] Comparative Example 1 A positive electrode was prepared in the same manner as in Example 1, except that the slurry was prepared without further mixing with the 0.1 M Al2(SO4)3 aqueous solution.

[0068] Experimental Example Experimental Example 1: Thermogravimetric analysis of sulfur-carbon composites In order to confirm the weight of sulfur in the sulfur-carbon composite produced in Example 1, a thermogravimetric analysis was performed, and the results are shown in Figure 1. The analysis apparatus and analysis conditions are as follows.

[0069] <Thermogravimetric analysis> Analyzer: Shimadzu TA 50 Analysis conditions: Argon 10mL / min, heating rate 5℃ / min, maximum temperature 600℃ 1, it was confirmed that the weight ratio of the porous carbon material (Ketjen Black) to sulfur in the sulfur-carbon composite (S / KB) prepared in Example 1 was about 33:67.

[0070] Experimental Example 2: Thermogravimetric analysis of polyacrylic acid binder with fixed polyvalent metal ions Polyacrylic acid (PAA) and 0.1M Al2(SO4)3 or 0.2M ZnSO4 were stirred at room temperature in a molar ratio of 1:1 (moles of polyacrylic acid monomer:moles of Al2(SO4)3 or ZnSO4), dialyzed for two weeks, and then dried at 60℃. Thermogravimetric analysis was performed to confirm the amount of polyvalent metal ions remaining in the binder, and the results are shown in Figure 2. The analytical equipment and conditions are as follows:

[0071] <Thermogravimetric analysis> Analyzer: Shimadzu TA 50 Analysis conditions: oxygen 10mL / min, heating rate 5℃ / min, maximum temperature 600℃ According to FIG. 2, after the thermogravimetric analysis, the remaining amount of Al2(SO4)3-PAA was confirmed to be 6.9%, and the remaining amount of ZnSO4-PAA was confirmed to be 8.3%. The remaining amount is related to the amount of metal that is not removed when equilibrium is reached with an excess amount of solvent, and considering that the thermogravimetric analysis is carried out in an oxygen atmosphere, the amount of the metal is measured in the form of oxide. That is, the remaining amount of 6.9% in Al2(SO4)3-PAA means the amount of Al2O3, and the remaining amount of 8.3% in ZnSO4-PAA means the amount of ZnO. As a result of the thermogravimetric analysis, it was confirmed that polyacrylic acid fixes a certain level of polyvalent metal (Al or Zn) through carboxylic acid functional groups.

[0072] Experimental Example 3: Capacity Retention Rate Analysis of Lithium-Sulfur Secondary Battery The positive electrodes manufactured according to the examples and comparative examples were prepared with a diameter of 14 mm, and a separator (Celgard® 2400, diameter 19 mm) and a negative electrode (Li chip, diameter 16 mm, thickness 160 μm) were laminated, and then placed in a coin battery case (2032 type coin cell (Wellcourse)) and an electrolyte was added to manufacture a coin cell. The electrolyte was a mixed solvent of 1,3-dioxolane (DOL) and dimethoxyethane (DME) to which 2M lithium bis(trifluoromethanesulfonyl)imide (LiTFSI) lithium salt and 0.1M LiNO3 were added.

[0073] The manufactured coin cell was charged and discharged to analyze the capacity retention, and the results are shown in Figure 3. The analysis device and analysis conditions are as follows.

[0074] <Cycle stability analysis> Analyzer: Wonatech WBCS3000L Analysis conditions: Charge / discharge at 0.5 A / g for the first three cycles, and then charge / discharge at 1 A / g.

[0075] 3, it was confirmed that the capacity retention rate due to cycling of the lithium-sulfur secondary battery was improved when the polyvalent metal salts according to Examples 1 to 3 were added. In particular, it was confirmed that the mid- to long-term cycle performance was improved when Al2(SO4)3 of Example 1 and MgSO4 of Example 2 were used, and that the initial cycle performance was improved when ZnSO4 of Example 3 was used.

[0076] Any mere variations or modifications of the present invention should belong to the scope of the present invention, and the specific scope of protection of the present invention will be made clear by the appended claims.

Claims

1. The battery includes a positive electrode active material, a conductive material, a binder, and a polyvalent metal salt, The positive electrode active material is a sulfur-carbon composite, the binder is a polymer compound having a functional group containing oxygen or nitrogen, The polyvalent metal salt is contained in an amount of 30 to 100 mol % based on the number of moles of the polymer monomer of the binder. The positive electrode for a lithium-sulfur secondary battery, wherein the polyvalent metal salt contains a cation selected from the group consisting of Mg 2+ , Al 3+ and Zn 2+ .

2. The polyvalent metal salt is Mg 2+ and Al 3+ and a cation selected from the group consisting of - , CO 3 2- , NO 3 - and S.O. 4 2- The positive electrode for a lithium-sulfur secondary battery according to claim 1, further comprising an anion selected from the group consisting of:

3. 2. The positive electrode for a lithium-sulfur secondary battery according to claim 1, wherein the binder is selected from the group consisting of polyacrylic acid, polyvinyl alcohol, polyacrylonitrile, and combinations thereof.

4. 4. The positive electrode for a lithium-sulfur secondary battery according to claim 1, wherein the polyvalent metal salt is contained in an amount of 40 to 100 mol % based on the number of moles of the polymer monomer of the binder.

5. The positive electrode for a lithium-sulfur secondary battery according to any one of claims 1 to 4, wherein the binder is contained in an amount of 5 to 20 wt % based on the total weight of the positive electrode active material.

6. The positive electrode for a lithium-sulfur secondary battery according to any one of claims 1 to 5, wherein the conductive material is selected from the group consisting of graphite, carbon black, conductive fibers, metal powder, carbon fluoride, conductive whiskers, conductive metal oxides, polyphenylene derivatives, and combinations thereof.

7. The positive electrode for a lithium-sulfur secondary battery according to any one of claims 1 to 6, wherein the conductive material is contained in an amount of 5 to 20 wt % based on the total weight of the positive electrode active material.

8. A method for producing a positive electrode for a lithium-sulfur secondary battery according to any one of claims 1 to 7, The method for producing a positive electrode for a lithium-sulfur secondary battery, wherein the polyvalent metal salt is added in the form of an aqueous solution and then dried before being introduced into the positive electrode.

9. 9. The method of claim 8, wherein the polyvalent metal salt in the aqueous solution state is added before the mixture of the positive electrode active material, the conductive material, and the binder is dried, or is applied after the mixture is dried.

10. A lithium-sulfur secondary battery comprising the positive electrode according to any one of claims 1 to 7.

Citation Information

Patent Citations

  • Preparation method of porous positive pole piece for lithium-sulfur battery and product thereof

    CN111029526A

  • Silicon dioxide sulfur positive electrode rich in aluminum hydroxyl and preparation method thereof

    CN111276683A

  • Positive electrode active substance composition for lithium secondary battery

    JP2002358967A

  • Multi-component electrodes for rechargeable batteries

    JP2013528913A

  • Binder for lithium-sulfur battery, positive electrode containing same, and lithium-sulfur battery

    JP2020532847A